High genetic diversity of HIV-1 pol region and molecular transmission networks among people living with HIV-1 in Haikou, South China, 2005–2022 - Dee Yu; Mu Li; Liangjia Wei; Kaokao Zhu; Rongjing Zhang; Tong Luo; Yi Ning; Hao Liang; Jing Zhang; Li Ye; Bingyu Liang (BMC Infectious Diseases)
Abstract Background Hainan is experiencing a continuous increase in newly diagnosed HIV-1 infections, highlighting the need for a comprehensive understanding of local transmission dynamics. This study aims to elucidate the genetic diversity and potential HIV-1 molecular transmission networks among people living with HIV-1 in Hainan, China. Methods We used the HIV-TRACE to infer the transmission dynamics of HIV-1 at a 1.5% gene distance threshold. The role of HIV-1 diversity in transmission networks was assessed through node influence measurement and centrality analysis. Results A total of 986 pol sequences were included, with CRF07_BC (43.71%) and CRF01_AE (37.12%) emerging as the predominant subtypes. Of these, 586 (59.43%) were clustered into the transmission networks, forming 83 clusters with 155 nodes having high transmission network scores (HTNS). CRF07_BC (adjusted odds ratio, aOR: 1.585, 95%CI: 1.189– 2.113) and CRF65_cpx (aOR: 9.513, 95%CI: 3.694– 24.499) were more likely to cluster in networks and exhibit nodal centrality than CRF01_AE. The CRF65_cpx (88.46%) were more likely to be HTNS (aOR: 57.302, 95%CI:16.869– 194.643) than CRF07_BC. Conclusion This study highlights the high genetic diversity of HIV-1 and its central role in transmission networks, advocating for targeted prevention strategies and community engagement for high-risk transmission populations, particularly focusing on subtypes CRF07_BC and CRF65_cpx.